Transit pollution exposure monitoring using low-cost wearable sensors. (September 2021) - Motlagh, Naser Hossein; Zaidan, Martha A.; Fung, Pak L.; Lagerspetz, Eemil; Aula, Kasimir; Varjonen, Samu; Siekkinen, Matti; Rebeiro-Hargrave, Andrew; Petäjä, Tuukka; Matsumi, Yutaka; Kulmala, Markku; Hussein, Tareq; et al.
Highlights: Wearable low-cost sensors are a viable solution for transport pollution monitoring. Novel wearable sensor for monitoring personal exposure during commuting. Our sensor is accurate (R  = 0.78) and consistent (R  > 0.98). Our sensor captures variations caused by route, passenger count and sensor location. Low-cost sensors support new applications and multiple stakeholders. Abstract: Transit activities are a significant contributor to a person's daily exposure to pollutants. Currently obtaining accurate information about the personal exposure of a commuter is challenging as existing solutions either have a coarse monitoring resolution that omits subtle variations in pollutant concentrations or are laborious and costly to use. We contribute by systematically analysing the feasibility of using wearable low-cost pollution sensors for capturing the total exposure of commuters. Through extensive experiments carried out in the Helsinki metropolitan region, we demonstrate that low-cost sensors can capture the overall exposure with sufficient accuracy, while at the same time providing insights into variations within transport modalities. We also demonstrate that wearable sensors can capture subtle variations caused by differing routes, passenger density, location within a carriage, and other factors. For example, we demonstrate that location within the vehicle carriage can result in up to 25 % increase in daily pollution exposure – a significant difference that existing solutions are unable to capture. Finally, we highlight the practical benefits of low-cost sensors as a pollution monitoring solution by introducing applications that are enabled by low-cost wearable sensors.